The efficacy of treadmill training on walking and quality of life of adults with spastic cerebral palsy: A randomized controlled trial - Bahrami, Fariba; Noorizadeh Dehkordi, Shohreh; Dadgoo, Mehdi (Iranian Journal of Child Neurology, 2019)
Abstract Objectives: We aimed to evaluate the efficacy of treadmill training on walkings peed and endurance and quality of life in ambulatory adults with spastic cerebral palsy (CP) versus traditional physiotherapy. Material & Methods, Participants (17 men, 13 women; mean (SD) age 25y, 9m (7y, 10m) range 18y- 45y) with GMFCS levels I, II, and III, from the Ra’ad Rehabilitation Goodwill Complex, randomly allocated to the experimental and the control groups. The trainings (treadmill for experimental group and conventional physiotherapy for control group) conducted two times a week for 8 consecutive weeks. Main outcome measures were the 10 meter walk test for the gait speed, the 6 minute walk test for the gait endurance and the WHOQOL- Brief questionnaire for the quality of life. Assessments had done at the baseline, ninth and 16th session (three times) during the treatment. Results: Although the experimental group showed a significant improve in the gait speed [1.08(0.47)m/s to 1.22(0.50)m/s](P=0.004) and in the gait endurance [291.13(160.28)m to 342.63(174.62)]( P=0/002), but between groups changes of the outcome measures of walking and quality of life were not significant. Conclusions: Treadmill training without body weight support would be no more effective than traditional physiotherapy to improve gait speed and endurance and quality of life in adults with spastic cerebral palsy. There is a hope to improve walking performance and function in adults with cerebral palsy.